Roblox Addiction and The Role of Escapism Among Emerging Adults in Jabodetabek - Linda Wati; Alleshandra Atthaya Vebrina AS (Psychological Research and Intervention, 2025)
Online games can make users feel happy because it offers a sense of psychological satisfaction such as not thinking about social pressure, anxiety, frustration, and it gives happiness. Online games are currently widely used among certain groups in Indonesia  such  as  Roblox.  Online  gaming  addiction  is  a  condition  in  which individuals  feel  an  excessive  dependence  on  online  games,  potentially  causing negative effects on themselves, while escapism is a condition in which a person has a desire or tendency to avoid reality by seeking entertainment and peace of mind. This study aims to examine the relationship between escapism and online gaming addiction by distinguishing two dimensions of motivation, self-expansion and self- suppression. This study uses a quantitative method with participants aged 18-29 lives in Jakarta, Bogor, Depok, Tangerang, or Bekasi. The participants in this study were individuals in states emerging adulthood who played Roblox for at least 4 hours a day. The measurement tools used in this study were the Gaming Addiction Scale by Lemmens et al. (2009) with 7 dimensions and the Escapism Motivation Scale by Stenseng et al. (2021) with 2 dimensions. The results of this study show a significant positive correlation between the Self-Suppression dimension and Online Gaming Addiction (r = 0.594). Individuals who escape based on the pressures or problems (self-suppression) they tend to have an increased level of addiction to online games.